Elected member of European Association of Extended Realities - Michael-Grigoriou, Despina (My University, 2026)
Elected as a member of the European Association of Extended Realities from the General Assembly of the Association. The elections took place by the General Assembly of the association from 6th to 10th of November 2024 with secret balloting and the position is for a three years term. The results were announced at the Ordinary General Meeting of the Association that took place in 28th November 2024 at the EuroXR 2024 conference venue.
Keywords: Sciences